2014
DOI: 10.5194/os-10-513-2014
|View full text |Cite
|
Sign up to set email alerts
|

Extreme winter 2012 in the Adriatic: an example of climatic effect on the BiOS rhythm

Abstract: Abstract. Adriatic and Ionian seas are Mediterranean subbasins linked through the Bimodal Oscillating System mechanism responsible for decadal reversals of the Ionian basinwide circulation. Altimetric maps showed that the last cyclonic mode started in 2011 but unexpectedly in 2012 reversed to anticyclonic. We related this "premature" inversion to the extremely strong winter in 2012, which caused the formation of very dense Adriatic waters, flooding Ionian flanks in May and inverting the bottom pressure gradien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
109
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(125 citation statements)
references
References 24 publications
11
109
0
1
Order By: Relevance
“…In the cyclonic pattern (Fig. 3a), the depth of the isopycnal 28.9 kg m −3 ranges between 40 and 120 m north of 37 • N. South of 37 • N, a steep gradient, implying isopycnal southward deepening, is observed consistently with the position of the mid-Ionian jet, which is reinforced during the cyclonic regime of the NIG (Bessieres et al, 2013;Gačić et al, 2014). The shallowest isopycnals are located around 39 • N and 18 • E, offshore of the Italian coast, representing the center of the cyclone.…”
Section: Physical and Chemical Characterization Of The Nigmentioning
confidence: 69%
See 2 more Smart Citations
“…In the cyclonic pattern (Fig. 3a), the depth of the isopycnal 28.9 kg m −3 ranges between 40 and 120 m north of 37 • N. South of 37 • N, a steep gradient, implying isopycnal southward deepening, is observed consistently with the position of the mid-Ionian jet, which is reinforced during the cyclonic regime of the NIG (Bessieres et al, 2013;Gačić et al, 2014). The shallowest isopycnals are located around 39 • N and 18 • E, offshore of the Italian coast, representing the center of the cyclone.…”
Section: Physical and Chemical Characterization Of The Nigmentioning
confidence: 69%
“…It has been demonstrated that this algorithm overestimates by a factor close to 2 [Chl a] in oligotrophic conditions ([Chl a] < 0.4 mg m −3 ) and alternative algorithms have been developed for the Mediterranean Sea (Bricaud et al, 2002;Volpe et al, 2007 The SSALTO-Duacs delayed-time maps of the absolute dynamic topography (ADT) (Rio et al, 2007) for the Mediterranean Sea (1/8 • ) computed and distributed by AVISO (http://www.aviso.altimetry.fr/, last access: January 2016) were downloaded for the period 1993-2014. As proposed by Gačić et al (2014), the sea level gradient between the north and the center of the NIG was used to determine the cyclonic-anticyclonic nature of the NIG circulation. In practice, the ADT difference between rectangles S2 (18.75-19.25 • E and 39.5-40 • N; see Fig.…”
Section: Satellite and Modeling Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Following Aegean activation, the mode 2 type circulation was re-established. The AIS eastward flow was restored, the upper thermocline salinities in the eastern part of the EMed decreased after 2010, and the upper Ionian Sea circulation in 2011 reversed once more to cyclonic [Gačić et al,2014] What is the role of the atmosphere during these events? To address these questions, we investigate the long-term atmospheric forcing variability and its influence on the thermohaline functioning of the Aegean Sea.…”
Section: Events Of Dciw Outflow and ''Emt-like'' Episodes And Their Rmentioning
confidence: 99%
“…AW intrusion into the Levantine basin is very variable and may depend on the circulation present in the Ionian (Gačić et al, 2010). In 2011 the NIG circulation was just reversing to cyclonic, as reported in Gačić et al (2014). Previously, the main effect of ∼ 5 years of anticyclonic NIG (2006NIG ( -2010, when the AW meandered in the northernmost part of the Ionian Sea, was a general increase in salinity in the Levantine basin (see the long-term analysis and discussion in Sect.…”
Section: Thermohaline Conditionsmentioning
confidence: 83%